BLOOD AND MEAT CHOLESTEROL LEVELS OF MALE BALI DUCK WHICH GIVEN COMMERCIAL RATION SUPPLEMENTED WITH PAPAYA LEAF ( Carica papaya L ) MEAL - Siti, Ni wayan; Sudana, I.B.; Budaarsa, Komang; Gaga Partama, I.B. (E-Journal Of Animal Science Udayana University, 2014)
An experiment was carried out to study the  levels of blood and meat cholesterol of male bali duck fed commercial diets supplemented papaya leaf (Carica papaya L) meal, in the Bali Provincial Laboratory. The design was completely randomized design (CRD) with 4 treatments and 5 replications. The fourth treatment were100 % commercial ration without papaya leaf meal (A) ; 98% commercial ration supplemented 2% papaya leaf meal ( B ) ;  96% commercial ration  supplemented 4 % papaya leaf meal (C) and 94 % commercial ration supplemented 6 % papaya leaf meal (D). The variables measured were total cholesterol, triglycerides, LDL and HDL blood and meat of male bali duck. The results showed that papaya leaf meal supplemented in the commercial ration from 2-6 % can significantly reduced total cholesterol, triglycerides and LDL, and increased HDL blood and meat of male bali duck. From the results of this study it be concluded that papaya leaf meal supplemented in commercial ration 2-6 % can reduced total cholesterol, triglycerides and LDL, and increased HDL blood and meat of male bali duck.